2005
DOI: 10.4040/jkan.2005.35.6.1125
|View full text |Cite
|
Sign up to set email alerts
|

The Daily Experiences of People with Chronic Schizophrenia

Abstract: The results of this study indicate that the experience of a chronic schizophrenic patient is like that of a miner caught under a fallen mine channel, who, without external help cannot escape the depths of the mine, but at the same time must have conviction and hope of rescue and avert fear to cooperate with outside help. The result indicates that family members, doctors and nurses as well as an institute's persistent and active support is most critical for the patient's adjustment to social life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…According to result [3,6,20] saying that even through mentally disabled's sexual life by being encouraged [26]. Similar to Min [10]'s study, the subjects of study are also observed putting an effort to seek for the meaning of disease affecting themselves and accept the single life in positive way.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…According to result [3,6,20] saying that even through mentally disabled's sexual life by being encouraged [26]. Similar to Min [10]'s study, the subjects of study are also observed putting an effort to seek for the meaning of disease affecting themselves and accept the single life in positive way.…”
Section: Discussionmentioning
confidence: 82%
“…Besides, it is dominant that the method of the studies analyzes it from objective views with valuables [10,27]. However, it begins that these point of views are recognized as a limit to understand the patient by when considering Nursing philosophy, person-centeredness comprehensive nursing care.…”
Section: Needs Of Studymentioning
confidence: 99%
“…선의적인 또는 악의적인 환청의 내용에 따라 환자들 은 그것을 받아들이고 환청의 지시에 따르는가 하면, 저항하고 불안감을 느끼기도 한다 (Min, 2005;Sayer, Ritter, & Gournay, 2000). 이렇게 환청이 미치는 영향이 크기 때문에 정신분 열병 환자에게 환청 관리는 매우 중요한 부분이다.…”
Section: 이상한 행동을 하여 가족이나 친구들과 멀어져 지속적인 인간unclassified